2011
DOI: 10.1027/1901-2276/a000024
|View full text |Cite
|
Sign up to set email alerts
|

A randomized-controlled pilot study of Epstein’s family-based behavioural treatment for childhood obesity in a clinical setting in Iceland

Abstract: A randomized-controlled pilot study of Epstein's family-based behavioural treatment for childhood obesity in a clinical setting in Iceland

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 22 publications
0
21
0
8
Order By: Relevance
“…Of these, 21 were considered acceptable (α > 0.70). TRT reliability was performed in 12 studies, 73,77,[80][81][82][83][84][85][86][87][88][89] also demonstrating high correlations (r = 0.58-0.81). Results from inter-rater reliability testing, however, were less strong; this was assessed in five studies, 81,90-93 three of which compared child self-report with parent report.…”
Section: Eating Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 21 were considered acceptable (α > 0.70). TRT reliability was performed in 12 studies, 73,77,[80][81][82][83][84][85][86][87][88][89] also demonstrating high correlations (r = 0.58-0.81). Results from inter-rater reliability testing, however, were less strong; this was assessed in five studies, 81,90-93 three of which compared child self-report with parent report.…”
Section: Eating Behaviourmentioning
confidence: 99%
“…Of these, eight papers 73,74,77,79,80,85,94 had all factors classed as acceptable (> 0.40) (see Appendix 8). Where appropriate, findings were used to make alterations to items and/or scales.…”
Section: Eating Behaviourmentioning
confidence: 99%
“…The behavioral economics model of obesity has been found to provide a particularly good framework for overcoming resistance to change in overweight children and adolescents [49] and was also associated with good long-term outcomes [50, 51]. In Iceland the Epstein model has been adapted and tested by Gunnarsdottir [52] and was found to be acceptable and effective in twenty children with overweight or obesity in a diverse sample. However, the Norwegian national guidelines did not recommend a special treatment program to be preferred and used but reported diverse evidence levels from A–D according to each initiative mentioned.…”
Section: The “Healthy Future” Studymentioning
confidence: 99%
“…For that reason limited data exist on the effects of FBBT among children with co‐morbid problems. Furthermore, limited data exist on its effects outside of the USA although two small pilot studies have shown promise among European outpatient samples [5,6]. A small uncontrolled pilot study from Britain ( n = 33) demonstrated FBBT to be both acceptable and effective in the short term [5].…”
Section: Introductionmentioning
confidence: 99%
“…A small uncontrolled pilot study from Britain ( n = 33) demonstrated FBBT to be both acceptable and effective in the short term [5]. Also, a randomized‐controlled pilot study from Iceland ( n = 16) suggested treatment was more effective than standard care and for children who were followed up treatment effects were maintained 1 year post treatment [6]. Although these studies indicate the potential effectiveness of Epstein's FBBT in clinical settings outside of the USA the results need to be replicated in a larger sample.…”
Section: Introductionmentioning
confidence: 99%